Determination of the occurrences, distribution, and health impacts of organohalogenated contamination of agricultural soils from Wuhan, Central China - Tekleweini Gereslassie; Muhamed Adem (Heliyon)
Organohalogenated compounds are among the persistent and ubiquitous organic pollutants in the environment. This study aimed to investigate the concentration, ecological, and human health impacts of persistent organohalogenated compounds in soil from Huangpi, Wuhan. Eighteen soil samples were collected from 0 to 10 cm and 10–20 cm depths. The quantification of seven indicator polychlorinated biphenyls (PCBs) and seven polybrominated diphenyl ethers (PBDEs) was performed using an Agilent gas chromatograph coupled with an electron capture detector. The obtained concentrations of Σ7PCBs ranged from 0.00 to 54.12 ng g−1 dry weight (dw) in the 0−10 cm depth and from 0.00 to 35.35 ng g−1dw in the 10−20 cm depth, with PCB-28 and PCB-52 being the frequently detected congeners. The Σ7PBDEs ranged from 0.00 to 34.88 ng g−1dw in the 0−10 cm depth and from 0.00 to 32.43 ng g−1dw in the 10−20 cm depth, with PBDE-47 and PBDE-28 being the most commonly detected congeners. Residues of the target compounds were detected in the study area. The concentrations of all the congeners considered in this study were below the ceiling ecological quality guideline limits. The estimated carcinogenic and non-carcinogenic health impact values indicated that the current levels of organohalogenated residues in the soil pose a negligible health risk to residents.